A novel rapid detection method for Salmonella based on NMR macromolecular Gd biosensor. (15th December 2022) - Dong, Qiuling; Yue, Xianglin; Li, Shuang; Hu, Mengna; Gao, Xiaoyu; Yang, Mingqi; Huang, Ganhui; Xiong, Chunhong; Fu, Guiming; Zhang, Jinsheng
Abstract: Rapid and efficient detection of foodborne pathogens is an important means of disease prevention. In this study, a low field NMR (Nuclear magnetic resonance) biosensor based on high density carboxyl polyacrylate targeting Gadolinium (Gd) probe was developed for rapid detection of Salmonella in milk. First, with activated polyacrylic acid and the streptavidinylated polyacrylic acid (SA-PAA) was obtained through amide reaction. The streptavidinylated magnetic complex (SA-PAA-Gd) was obtained by utilizing the chelating adsorption properties of PAA for gadolinium. The magnetic complex binds to the biochemical antibody with high affinity, and finally obtains the target probe. The probe captures Salmonella through antigen-antibody interaction, and the longitudinal relaxation time ( T 1 ) was obtained by NMR. This biosensor the sensitivity of detecting Salmonella within 1.5 h is 3.3 × 10 3 CFU/ml. It is very likely to become a novel and interesting method for rapid detection of Salmonella, and its application prospect is broad. Highlights: A PAA@Gd - based NMR immunosensor was developed to detect salmonella. The PAA skeleton is chelated with Gd to achieve the amplified output of the magnetic signal. The biotin-streptavidin system enables double amplification of the magnetic signal in the probe. The NMR biosensor is easy to operate, has a low detection limit, and effectively shortens the detection speed. The constructed detection platform provides the possibility for the detection of other strains.